Arabic Teaching Curriculum for Indonesian General Educational Stages in the Society Era 5.0 - Harisca, Rodhy; Muslim, Ahmad Bukhari; Moalim Shariif, Abdulahi Hussein (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Arabic is the key to understand Islamic teachings and one of the international world languages of United Nations. However, Arabic learning in Indonesia had not reached the goals of mastering Arabic as a whole yet. The objective of this article was to reformulate Arabic teaching curriculum for Indonesian general educational stages in the society era 5.0. The importunateness of this article was to investigate the  development of Arabic teaching. Descriptive method was adopted in this article. Literature study was used in the data collection technique with four steps by Zed, such as collecting the data, conceptualizing the data, analyzing data and interpreting the data. The source of the data were the three books as the principles of constructive theories in this field; these books are: Manahij al-Lughah al-’Arabiyyah wa Tharaiq Tadrisiha, al-Lughah al-‘Arabiyyah li an-Nathiqin bi Ghairiha Dalil Tathbiqi and Second Language Acquisition. Other related books were also used beside the principle books to arrange the article topic. The article findings indicated that optimizing second language acquisition and developing language skills were the most important things to be a focus supported by technology and media in reformulating Arabic teaching curriculum for Indonesian general educational stages in the society era 5.0. The further research was recommended in reformulating of the Arabic teaching curriculum for each educational stage based on this article findings.